P14.74 Grade II and III pleomorfic xanthoastrocitoma: a monocentric, retrospective analysis. (9th September 2021) - Gaviani, P; Simonetti, G; Farinotti, M; Redaelli, V; Botturi, A; Pollo, B; Legnani, F; Pinzi, V; Silvani, A
Abstract: BACKGROUND: Pleomorphic xanthoastrocytoma (PXA) represent an astrocytic neoplasm that is typically well circumscribed and can have a relatively favorable prognosis. Tumor progression to anaplastic PXA (WHO grade III), however, is associated with a more aggressive biologic behavior and worse prognosis. The factors that drive anaplastic progression are largely unknown. The activating BRAF mutation is a genetic alteration that could be present in both PXA and anaplastic PXA; Identification of the mutation can be important as BRAF V600E mutant protein could be targeted therapeutically by small molecule inhibitors of both RAF and MEK. The low frequency of these tumors has fostered heterogeneity of therapeutic approaches, particularly in adult patients. We performed a monocentric, retrospective study on adult patients with a PXA diagnosis treated by our Institution, in order to search for markers of diagnosis and prognosis. MATERIAL AND METHODS: All consecutive patients older than 18 years with a histological diagnosis of a primary grade II and III pleomorphic xanthoastrocytoma operated and treated by our Institution from 2011 to 2021 were consecutively and retrospectively included in the study. All pathological diagnoses and PXA cases were reviewed according to the WHO classification. Histological and molecular characteristics, including BRAF mutation status, as well as clinical data, treatment modalities, and patient outcome were analyzed and described. RESULTS: 21 patients were included, 10 males and 11 females, with a median age of 40 years old (range 18–66). In 10 patients the histology showed an anaplastic PXA and in 11 patients a grade II tumor. Genetic features, including IDH status were available to all patients and BRAF mutation study was available in 8/10 anaplastic PXA. All patients underwent main surgery. Anaplastic features were associated with minimal PFS, whereas BRAF mutation tended to be associated with a better PFS. CONCLUSION: Anaplastic features and BRAF mutation can lead to identify subgroups with distinct prognosis. These results should be validated in a larger and prospective study.